Patterns of Epidural Venous Varicosity in Lumbar Stenosis - Ju, Jeong-Hyuk (Korean J Spine, 2012)
OBJECTIVE: Epidural venous varicosity (congestion of the epidural vein) is rarely introduced as an influential factor of clinical symptoms. However, there are several studies suggesting that epidural venous varicosity results in neurologic symptoms. We would like to highlight evidence that epidural venous varicosity results in neurologic symptoms and the relation between epidural venous varicosity and neural structure observed during the surgery. Based on our experiences, we also propose a new classification of epidural venous varicosity. METHODS: 29 patients with symptomatic lumbar stenosis received microsurgical decompression via partial hemilaminectomy. The authors retrospectively reviewed all recorded intraoperative pictures and categorized patterns of venous varicosities with relationship to neural structures. RESULTS: Type A is conditions in which epidural veins are dilated but located parallel to the nerve root on the lateral side of the nerve root and thus do not compress the nerve root. Type B is conditions in which varices are located on the anterior lateral side of the nerve root to compress the nerve root. Type C is conditions in which varices are encircled around the nerve root and compressing the nerve root. CONCLUSION: Epidural venous varicosity is observed in most lumbar stenosis patients with clinical symptoms. Of the types, the types of epidural venous varicosity compressing nerve structures were Type B and Type C. All epidural venous varicosities were removed regardless of classification during operations. Most patients showed relief in clinical symptoms after the operation. We thought to epidural venous varicosity as a factor that causes clinical symptoms of lumbar stenosis.